Challenges faced by RPL teachers in implementing ICT-based curriculum - Ali Zainal Abidin Zaky (Himpunan Pengembang Kurikulum Indonesia, 2026)
An industry-relevant vocational curriculum requires Rekayasa Perangkat Lunak (RPL) teachers to adapt their learning to the latest Information and Communication Technology (ICT)-based curriculum. This study aims to identify the specific challenges faced by RPL teachers in implementing an ICT-based curriculum in vocational high schools. A descriptive qualitative approach was used, employing in-depth interviews and observations with RPL teachers in public vocational high schools. The main results revealed significant challenges, including limited essential technological infrastructure and human resource readiness, including gaps in students' digital competencies and a lack of ongoing teacher training relevant to RPL. Furthermore, dynamic curriculum changes are often not matched by school facilities and funding, and are characterized by high administrative burdens for teachers. This study makes an original contribution by mapping in detail how these challenges, while partially reinforcing general findings, manifest uniquely and in context for RPL teachers in implementing the Independent Curriculum. These findings are expected to provide an important foundation for formulating more targeted teacher training and developing strategies for implementing an effective and digitally responsive vocational curriculum. Abstrak Kurikulum kejuruan yang relevan dengan industri mengharuskan guru Rekayasa Perangkat Lunak (RPL) mengadaptasi pembelajaran sesuai dengan kurikulum terkini berbasis Teknologi Informasi dan Komunikasi (TIK). Penelitian ini bertujuan untuk mengidentifikasi secara mendalam tantangan spesifik guru RPL dalam implementasi kurikulum berbasis TIK di Sekolah Menengah Kejuruan (SMK). Metode kualitatif deskriptif digunakan, melalui wawancara mendalam dan observasi kepada guru RPL di SMK Negeri. Hasil utama mengungkapkan tantangan signifikan yang meliputi keterbatasan infrastruktur teknologi esensial dan kesiapan SDM, termasuk kesenjangan kompetensi digital murid serta kurangnya pelatihan guru berkelanjutan yang relevan untuk RPL. Selain itu, perubahan kurikulum yang dinamis sering kali tidak diimbangi oleh kesiapan fasilitas dan pendanaan sekolah, serta diwarnai oleh tingginya beban administratif bagi para guru. Studi ini berkontribusi secara orisinal dengan memetakan secara detail bagaimana tantangan ini, meski sebagian menguatkan temuan umum, termanifestasi secara unik dan kontekstual pada guru RPL dalam implementasi Kurikulum Merdeka. Temuan ini diharapkan menjadi landasan penting bagi perumusan pelatihan guru yang lebih terarah serta pengembangan strategi implementasi kurikulum vokasi yang efektif dan responsif terhadap dinamika digital. Kata Kunci: kurikulum RPL; pembelajaran berbasis TIK; tantangan guru